A Historiographical Dimension of Generic Relationships of the Category “Social Expectations” - Popovych, Ihor; Langer, Phil (Journal of Education Culture and Society, 2026)
Aim. The aim is to examine a historiographical dimension of generic relationships of the category “social expectations”; determine the initial scientific category; and create a graphical visualisation of social expectations of an individual in a historical dimension. Methods. The paper presents a retrospective analysis of social expectations of an individual. Results. It highlights that historiographical scientific research and investigation of the source literature allowed for identifying an incredibly huge array of the concepts under study. The research establishes generic relationships of the category “social expectations” in the dimensions of the source literature of the global scientific theory and practice. It substantiates the preconditions and the features of the origin and development of the scientific category “social expectations”. The research determines the initial scientific category under study as the basis for the development of the category “social expectations”. It presents a graphical visualisation of the category “social expectations” in a historiographical dimension of the research. Conclusions. The study generalises the complexity and importance of the research for modern science. It outlines a historical aspect of the investigation of the category “social expectations” and determines the range of usage, differentiating it from other concepts similar in content and scope.